Management of postoperative pain in Spain: a nationwide survey of practice. Issue 5 (5th March 2017) - Montes, A.; Aguilar, J. L.; Benito, M. C.; Caba, F.; Margarit, C.; ,
Abstract : Background: Although the need for structured assessment and management of acute postoperative pain has been recognized, practices and responsibilities vary between and within hospitals and countries. We sought to determine current pain management practices in Spanish hospitals with and without acute pain services (APSs) or acute pain management programmes (APMPs) and compare them to practices reported for 1997–1998. Methods: Members of the Spanish Pain Society and APS/APMP heads were asked to respond to a survey. Responses were stratified by hospital size (< 200 or ≥ 200 beds) and APS/APMP presence or not. Categorical variables were described by percentages and the 95% confidence interval and continuous ones by the median and interquartile range. Results: Responses were received from 42.4% of hospitals with ≥ 200 beds (vs. 9.6% of the smaller ones). We fully analysed only data for the larger hospitals, 57.7% of which had an APS or APMP. Full‐time pain physicians were on staff in 28.6% of large hospitals; 25% had full‐time nurses. Patients received written information about postoperative pain in 34.8% of APS/APMP hospitals, and 72% of them recorded pain assessments routinely. Protocols reflected interdepartmental consensus in 80.8%; training in postoperative pain was organised in 54%. Respondents thought pain was well or very well managed in 46.4%. In APS/APMP hospitals the following results had improved: provision of written information for patients (58.5% vs. 0%), the recording of pain assessments (93% vs. 43.8%), consensus on a pain scale (92.5% vs. 41.9%), use of protocols (99.7% vs. 55.2%), analysis of quality indicators (52.8% vs. 15.4%), training (73% vs. 26.9%), and respondents' satisfaction with pain management in their hospital (68.6% vs. 9.5%). Conclusions: The presence of an APS or APMP is associated with better results on indicators of quality of acute postoperative pain management.